Pengaruh Akupresur terhadap Kadar Glukosa Darah Pasien Diabetes Melitus Tipe 2 di Persadia RS Islam Jakarta Cempaka Putih - Jumari Jumari; Agung Waluyo; Wati Jumaiyah; Dhea Natashia (Journal of Telenursing (JOTING), 2019)
This study aimed to identify the effect of acupressure on blood glucose levels in type 2 diabetes mellitus patients. This study used a quasi-experimental design with a pre-post test design approach. The results showed a significant difference in blood glucose levels between the intervention group and the control group (t = 4.22; p = 0.001). In conclusion, acupressure is an effective intervention to reduce blood glucose levels in patients with type 2 diabetes mellitus. Keywords: Acupressure, Type 2 Diabetes Mellitus, Blood Glucose Levels